Design Hybrid Algorithm for Video Encoding - Ghada Tahir Qasim; Toqa Zuhair; Sahar Saleh; Amena Emad (Al-Rafidain Journal of Computer Sciences and Mathematics)
The most of the related studies and researches have focused on encrypting video files on speed and accuracy in the process of encryption. Some of them have focused on reducing the time required for the calculations. Some of them have focused on increasing the privacy of the process of encryption, regardless the processes of calculations. Due to the fact that all the studies and researches that have been found were focused on the use of some  of the ways of encrypting the texts like data encryption standard (DES) in encrypting video files ,and the fact that all the weakness points were related to the calculations, so in this research, many of these methods were connected with modification required to reduce the calculations and to obtain the speed of encrypting video files and give them a high privacy. The research has been completed in five stages, four of which are used to provide four levels of protection with levels of internal protection to ensure high privacy. The fifth stage is to conduct the process of analyzing the code of the files that has been encrypted in the previous stages as show below: The first stage :using  the style of scrambling by using  a developed style by using a proposed function ,but not by using the style of texts, to ensure speed of performing this method. The second stage: Using the style of changing some color values to ensure high privacy. The third stage; Using the style of scrambling (column scrambling) to ensure a stage of higher privacy. The fourth stage: Using the scrambling method of the color values that bear higher frequency. The fifth stage :Analyzing the video files resulting from the process of encryption. As well as achieving an external protection for the program via checking the user ID and the used keys. It should be pointed out that the results of this  research has been achieved by using MATLAB 7 and MATLAB10 languages.